GEMES (Gerakan Masyarakat Cegah Stunting) di Posyandu Al-Munawaroh Desa Sungai Landai Kecamatan Mestong Kabupaten Muaro Jambi - Satiti Kawuri Putri; Dini Wulan Dari (Jurnal Abdimas Kesehatan (JAK), 2023)
Indonesia shows a relatively high prevalence of stunting, which was 27,67% in 2019 at the national level. Stunting or short stature in early childhood is a social health problem that must be addressed. The definition of stunting is that the height index according to age (TB/U) is less than minus two standard deviations (<-2 SD) compared to the growth standards of toddlers or having a height that is less than it should be achieved at a certain age. The occurrence of stunting begins in the first 1000 days of life (0–23 months) and continues until the age of 5 years. In children under the age of 5 years, stunting can cause impaired physical development, inhibition of mental growth, late motor development, and long-term effects on cognitive development until adulthood. Stunting can be prevented early, therefore the service team took the initiative to educate GEMES (Community Movement to Prevent Stunting) at Posyandu Al-Munawaroh, Sungai Landai Village, Mestong District, Muaro Jambi Regency. The method of service carried out is the provision of material on the meaning of 1000 HPK and an explanation of the causes, impacts, and prevention of stunting. Methods of implementing activities include planning, monitoring, and evaluation. The result of this service was an increase in the knowledge of mothers who had toddlers about the education provided related to GEMES from 56.3% (before being given education) to 88.8% (after education).